Clinical and prognostic significance of m6A hypomethylation and IGF2BP3 overexpression in gastric cancer: an integrated epigenomic-transcriptomic analysis - Xiangchen Hu; Zhe Wang; Youwei Kou; Yujing Huang (Human Genomics)
Abstract Background Gastric cancer (GC) ranks as the fifth most prevalent malignancy and the third leading cause of cancer-related mortality worldwide, with complex pathogenesis driven by genetic and epigenetic alterations. While genetic contributors to GC have been extensively studied, the functional role of N6-methyladenosine (m6A) RNA methylation—the most abundant eukaryotic RNA modification—in gastric carcinogenesis remains insufficiently characterized. This study aimed to investigate transcriptome-wide m6A methylation dysregulation and its mechanistic implications in GC progression. Methods Methylated RNA immunoprecipitation sequencing (MeRIP-seq) was performed to map m6A epitranscriptomes in paired GC and adjacent normal tissues. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were conducted on 253 hypomethylated mRNAs to delineate the biological pathways associated with m6A dysregulation. The transcriptomic profiles were analyzed using RNA-seq, while a retrospective cohort analysis (n = 58) evaluated the correlations between IGF2BP3 expression and the clinicopathological characteristics of patients with GC. Results MeRIP-seq analysis demonstrated transcriptome-wide m6A hypomethylation in GC tissues, identifying 271 significantly reduced peaks (p < 0.01). Functional annotation revealed enrichment of hypomethylated transcripts in metabolic pathways and transcriptional dysregulation. Notably, m6A-related genes exhibited widespread activation in GC, with IGF2BP3 showing the most pronounced upregulation (106-fold increase, p < 0.0001). Clinically, elevated IGF2BP3 expression significantly correlated with lymph node involvement (p = 0.016) and advanced TNM staging (p = 0.028). Conclusion This study establishes m6A methylation dysregulation as a critical mechanism in GC pathogenesis and identifies IGF2BP3 as both a potential therapeutic target and a prognostic biomarker in GC.